(untitled) (Research, Society and Development, 2021)
Introduction: Insulin-like growth factor binding protein -3 (IGFBP3) is the main mediator of IGF-1/IGF-1R binding, and may inhibit the binding between IGF-1 and IGF-1R and trigger cell growth suppression. Method: This study is a systematic review in which searches were conducted in Pubmed, Web of science, Science direct and Scopus databases for studies published in the period 2010-2020, including case-control studies that evaluated the association of polymorphisms in the IGFBP3 gene with cancer. Results: Of the 6 studies included, 5 were conducted in China and 1 in Iran, published in 2015 (n=2), 2014 (n=2), 2013 (n=1) and 2011 (n=1). In all, there were 5 types of cancer studied: esophagus (n=2), prostate (n=1), colorectal (n=1), breast (n=1) and gastric (n=1). In the studies chosen, 8 SNPs located in the IGFBP3 gene were evaluated: rs2854744, rs2854746, rs2132572, rs9282734, rs3110697, rs2960436, rs2270628 and rs10282088. Only the Zhao et al studies. (2015) and Liu et al. (2015) found a relationship between SNPs in the IGFBP3 gene with cancer. Two studies (Qian et al., 2014 and Qian et al., 2011) did not describe allelic frequencies in their results. Conclusion: Based on the studies we can demonstrate that the findings on the association of polymorphisms in the IGFBP3 gene with cancers are confusing, divergent and the role of the IGF pathway in carcinogenesis has not been clearly defined. However, the studies bring strong evidence that suggests possible relationships of this pathway and genetic variants with the carcinogenesis process in several types of cancer.